Age-associated features of oxidative stress as marker of vascular aging in comorbid course of hypertension and type 2 diabetes mellitus - Nemtsova, V. D.; Bilovol, Olexander; Ilchenko, Irina; Shalimova, Anna (OAE Publishing Inc., 2018)
Aim: To evaluate activity of oxidative stress (OS) as marker of vascular aging in different age groups of patients with combined course of arterial hypertension (HT) and type 2 diabetes mellitus (T2DM). Methods: 126 patients (average age 57.8 ±6.2 years) with stage II HT and compensated T2DM were divided into 2 subgroups: 2a (n= 59) - aged 45-60 years; 2b (n= 97) - aged 61-75 years; 30 patients with isolated stage II HT (comparison group), 20 practically healthy individuals (control group). The activity of antioxidative [glutathione peroxidase, sulfhydryl groups (SH-groups)] and oxidative [malonic dialdehyde (MDA)], 8-hydroxy-2-deoxyguanosine (8-OH-dG) systems in blood serum, were studied. Results: A significant increase in MDA levels (P< 0.05) and SH-groups (P< 0.05) compared with healthy volunteers was observed. Patients in 2b group had lower MDA values than in 2a (6.25 ±0.33 μmol/L, 7.07 ±0.44 μmol/L, respectively, P> 0.05). In the 2b group, in comparison with 2a patients, a decrease in thiol status was observed (P> 0.05). The level of 8-OH-dG was increased in patients with HT and T2DM, but there was also an age-associated increase in the average 8-OH-dG in the 2b group. Conclusion: The age-associated changes in the OS in comorbid course of HT and T2DM did not have significant differences. Nevertheless, the presence of correlations between various indexes that are included in the concept of “vascular aging” and indicators of oxidant-antioxidant systems in different age groups allows us to make an assumption about the significant influence of the oxidative status on the status of vascular age, especially in the older age group persons.
Keywords: Hypertension; type 2 diabetes mellitus; oxidative stress; vascular aging